2020
DOI: 10.17363/sstb.2020.36.4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Anxiety of Swimmers Regarding Contracting New Type of Coronavirus (Covid-19)

Abstract: Aim: In this study, it was aimed to investigate that anxiety of Swimmers about contracting new type of Coronavirus (Covid19). Method: Swimmers in active state in Turkish Swimming Federation participated in this study. The participants of this research consist of 247 female and 203 male swimmers (450 in total) who are in active state in Turkish Swimming Federation. In this study, “Personal Info Questionare” and “Anxiety of atheletes for contracting new type of Coronavirus (Covid-19) scale” developed by Demir et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Batu reported that (2020) the anxiety of swimming athletes catching Covid, it was determined that the anxiety levels of female athletes were higher than male athletes [28]. In the study, it was seen that there was no significant difference in the anxiety scores of the athletes when comparing the anxiety of catching Covid by gender, but the average score of women was higher than that of men.…”
Section: Discussionmentioning
confidence: 79%
“…Batu reported that (2020) the anxiety of swimming athletes catching Covid, it was determined that the anxiety levels of female athletes were higher than male athletes [28]. In the study, it was seen that there was no significant difference in the anxiety scores of the athletes when comparing the anxiety of catching Covid by gender, but the average score of women was higher than that of men.…”
Section: Discussionmentioning
confidence: 79%
“…As a result of the research of Batu and Aydın (2020), no significant difference has been seen between the anxiety of the athletes contracting Covid-19 and the income status variable of the athletes. Although these findings are in line with the findings of the current study, it can be thought that there is no difference in our country since individuals with low income and individuals with high income benefit from health services equally.…”
Section: Discussionmentioning
confidence: 92%